A Revolution for our Rights: Indigenous Struggles for Land and Justice in Bolivia, 1880-1952 - Spronk, Susan (Labour / Le Travail, 2009)
The article reviews the book, "A Revolution for Our Rights: Indigenous Struggles for Land and Justice in Bolivia, 1880-1952," by Laura Gotkowitz.
Keywords: BOOKS – Reviews; Book reviews; Business And Economics–Labor And Industrial Relations; GOTKOWITZ; Laura; History–History of North And South America; INDIGENOUS rights; Latin American history; Native rights; Nonfiction; REVOLUTION for Our Rights: Indigenous Struggles for Land & Justice in Bolivia 1880-1952; A (Book); Revolutions